Argument-driven inquiry in chemistry : lab investigations for grades 9-12 - Sampson, Victor, ....- (Arlington : NSTA Press, 2015)
Transform your chemistry labs with this guide to argument-driven inquiry. Designed to be much more authentic for instruction than traditional laboratory activities, the investigations in this book give high school students the opportunity to work the way scientists do. They learn to identify questions, develop models, collect and analyze data, generate arguments, and critique and revise their reports. Thirty field-tested labs cover a broad range of topics related to chemical reactions and matter's structure and properties. You can use them as introduction labs to acquaint students with new content or as application labs to try out a theory, law, or unifying concept. Like Argument-Driven Inquiry in Biology, this book was written by veteran teachers who made it easy to use and aligned with today's standards. All labs include reproducible student pages, teacher notes, and checkout questions. If you've been wanting to try an argument-driven approach to chemistry but haven't been sure how, this book will provide both the information and instructional materials you need to get started.
Keywords: Chemie -- Secundair onderwijs